Implikasi Penggunaan Bahan Berbahaya Dan Beracun (B3) Dalam Pemenuhan Kebutuhan Dasar Rumah Tangga Terhadap Lingkungan - Andre Rizaldy; Irwan Triadi (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
The 1945 Constitution or the Constitution states that a good living environment is everyone's right. This is regulated in Article 28H paragraph (1). Mutatis mutandis, a good living environment is everyone's constitutional right, in this caseIndonesian society cannot be reduced. The research method used in this writing is a normative juridical method with a literature study approach which is legal research that focuses on legal norms including principles, norms, rules, laws and regulations, agreements and doctrine. However, nowadays there is a lot of environmental damage due to the use of B3 materials (Hazardous and Toxic Substances) for household purposes either directly or indirectly, this can be a factor in the constitutional rights of a citizen whoThis action has been reduced, therefore in this article the author will discuss the implications for the environment in the use of B3 materials to meet needs.